Profile of Patients with Ear, Nose, and Throat Foreign Bodies on Emergency Room, RSUD Dr. Soetomo in 2018 - Raka Ihsanulhaj; Rizka Fathoni Perdana; Sahudi Abdul Mujib; Puguh Setyo Nugroho (Health Notions, 2021)
Foreign bodies in the ear, nose, and throat (ENT) is a common emergency case found in the emergency room. On 2016, it was found that 689 patients admitted to RSUD Dr. Soetomo’s emergency room due to foreign bodies on their ear, nose, or throat. This study aims to determine the profile of patients with foreign bodies on their ear, nose, or throat that admitted to Emergency Room, RSUD Dr. Soetomo in 2018. This type of research was a retrospective study using medical records of patients. The total of patients in this study was 802 patients. It was found that the most common foreign bodies was found on ear with 342 cases (42.64%), followed by nose with 265 cases (33.04%), and lastly throat with 195 cases (24.31%). The most common patients age group was 0-10 years with 376 cases (46.88%), followed by patients with age group more than 50 years with 93 cases (11.60%). There were more males patients with 445 patients (55.49%) rather than women with 357 patients (44.51%). The most common foreign bodies on ear was cotton with 173 cases (50.58%). The most common foreign bodies on nose was bead with 137 cases (51.70%). The most common foreign bodies on throat was fish bone with 166 cases (85.13%). The standard procedure for patients with foreign bodies was with extraction, extra procedure may be needed according to the condition of patients. Most of the patients showed no complication after the treatment. Keywords: foreign bodies; the ear, nose, and throat (ENT), profile of patients